Relationship between occupational noise exposure and hypertension: Cross-sectional evidence from real-world - Zhang, Ling; Chen, Siqi; Chen, Zhuowang; Yin, Wenjun; Fu, Wenjuan; He, Fang; Pan, Zhen; Yi, Guilin; Tan, Xiaodong (Frontiers in Public Health, 2022)
Background: Occupational noise is one of the most common and prevalent occupational hazards worldwide and may induce adverse auditory and/or non-auditory health effects. However, the relationship between occupational noise exposure and hypertension is controversial and has long been debated. Methods: Based on large sample cross-sectional data from all registered occupational health examination units from 2021 to 2022 (N=101,605), this study aimed to analyze the prevalence of hearing loss and hypertension and to explore the influencing factors of hypertension of workers in Wuhan. Descriptive statistics, univariate analyses and multivariate analyses were used. Forest plot and nomograms were constructed for the visualization of predictive results. The ROC curve, AUC, C-index and calibration curves were used to assess the predictive accuracy and validity. DCA was performed to evaluate the net benefit that workers could receive. Results: Higher rate of high-frequency hearing loss (25.3%), speech frequency hearing loss (8.8%), ECG abnormalities (31.9%) and hypertension (21.0%) were found in workers exposed to occupational noise in Wuhan. Occupational noise exposure (OR=1.09, 95%CI: 1.01-1.18, p=0.04), growth of age (OR: 1.07, 95%CI: 1.07-1.07, p＜0.001), overweight (OR: 1.82, 95%CI: 1.73-1.92, p＜0.001), obesity (OR: 3.62, 95%CI: 3.42-3.83, p＜0.001), hyperglycemia (OR: 1.84, 95%CI: 1.73-1.96, p＜0.001), hypercholesterolemia (OR=1.34; 95% CI 1.22-1.48; p＜0.001), ECG abnormalities (OR=1.11; 95% CI 1.07-1.15; p＜0.001) and family history of hypertension (OR=1.69; 95% CI 1.58-1.81; p＜0.001) were risk factors of hypertension for workers. Male workers had a relatively higher hypertension risk than female workers (OR=1.61; 95% CI 1.54-1.69; p＜0.001). Ear protective measures could not reduce the risk of hypertension in workers. Our nomogram has good predictive accuracy and validity. A dynamic nomogram to predict the workers’ risk of hypertension was established publicly available online. Conclusions: Occupational noise exposure may elevate workers’ hypertension risk. More effective and relevant prevention measures should be taken. Our nomogram may help identify high-risk workers and facilitate timely interventions.